Bankruptcy to billions : how the Indian railways transformed - Sudhir Kumar (New Delhi, 2009)
The Indian Railways is one of the world's largest state-owned enterprises with around 1.4 million employees, over 63,000 kilometres of network, running around 13,000 trains each day. Bankruptcy to Billions reveals for the first time how the Indian Railways transformed from near bankruptcy to post US$ 6 billion (Rs 25,000 crore) annual cash surplus in 2008.
Keywords: Railways transformation - India